The Effect of Using BSF Larvae in Kitchen Organic Waste Processing on Achieving Bioconversion Production at the Sahate Main Waste Bank in Pangandaran Regency - Fenty Rosmala (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
The management of organic kitchen waste from hotels and restaurants is an increasingly complex environmental problem, especially in tourist areas such as Pangandaran Regency. One innovation in sustainable organic waste management is the utilization of Black Soldier Fly (BSF) larvae through a bioconversion process to produce fresh maggots as high-protein animal feed. This study aims to analyze the effect of the use of BSF larvae in processing organic kitchen waste on the achievement of fresh maggot bioconversion production at the Sahate Main Waste Bank (BSI) in Pangandaran Regency. This study used a causal research design with a quantitative approach. Data collection methods were carried out through field observations and interviews, with data analyzed using normality tests, t-tests, and simple linear regression using SPSS software. During the 10-week research period, the total processed organic kitchen waste reached 44,969 kg, with a fresh maggot production of 5,644 kg. The analysis results showed that the use of BSF larvae had a positive and significant effect on the achievement of fresh maggot bioconversion production, as evidenced by a significance value of 0.001 (<0.05) and a calculated t-value of 8.793 (>2.306). The research findings also indicated that the scale and quality of kitchen organic waste play a significant role in increasing the effectiveness of bioconversion. This study concluded that the use of BSF larvae is an effective and sustainable method in processing kitchen organic waste and has the potential to support waste reduction while meeting the need for high-protein animal feed.